Characterization of Bozitinib as a potential therapeutic agent for MET-amplified gastric cancer - Hang Lin; Lingzhi Qu; Hudie Wei; Ming Guo; Xiaojuan Chen; Qianmeng Lin; Huajun Zhang; Shuyan Dai; Yongheng Chen (Communications Biology)
Abstract Hyperactive c-Met signaling pathway caused by altered MET is a common mechanism underlying gastric cancer and represents an attractive target for the treatment of gastric cancer with MET alterations. However, no c-Met kinase inhibitors are currently approved specifically for the treatment of c-Met-amplified gastric cancer. Recently, bozitinib, a highly selective c-Met kinase inhibitor, has shown remarkable potency in selectively inhibiting MET-altered non-small cell lung cancer and secondary glioblastoma. In this study, we investigate the antitumor activity of bozitinib against MET-amplified gastric cancer and elucidate its molecular mechanism. Bozitinib demonstrates a strong effect on MET-amplified gastric cancer cells by blocking the c-Met signaling pathway, leading to the inhibition of cell proliferation and survival, as well as the induction of G0/G1 phase arrest and apoptosis. Structurally, bozitinib is optimally embedded in the ATP pocket of c-Met and firmly binds via an extensive interaction network. In addition, bozitinib efficiently inhibits c-Met resistance-conferring mutations G1163R and Y1230H, although its potency is significantly decreased against the D1228N and Y1230C mutations. Overall, our study reveals the molecular mechanism of bozitinib against c-Met, highlights its ability to overcome acquired resistance mutations, and provides valuable insights into further design and improvement of selective c-Met inhibitors.